Penguatan Kepemimpinan Kepala Sekolah Menuju Sekolah Unggul - Ibrahim Bafadal; Ahmad Nurabadi; Juharyanto Juharyanto; Imam Gunawan (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Abstract: The problem faced by Mitra as a result of conversations with school or Madrasah principals is a lack of understanding how to carry out and optimize their leadership role. Many school principals still feel they need guidance and guidance in carrying out their leadership role in improving the quality of their school as a superior school. The output of this activity seeks to increase the understanding of 50 school principals regarding: 1) Principal Leadership in superior schools in a sustainable, independent and contextual manner; 2) Learning Leadership in superior schools in a sustainable, independent and contextual manner; 3) Religious Leadership in superior schools in a sustainable, independent and contextual manner; and 4) Change Leadership in superior schools in a sustainable, independent and contextual manner. The methods used in this service activity are: a) training, and b) mentoring. In general, the activities to strengthen the leadership of school principals towards superior schools can be carried out well. Abstrak: Permasalahan yang dihadapi oleh Mitra dari hasil percakapan dengan kepala sekolah atau Madrasah adalah kurangnya pemahaman bagaimana melaksanakan dan mengoptimalkan peran kepemimpinannya. Banyak Kepala Sekolah masih merasa memerlukan pembinaan dan pembimbingan dalam hal melaksanakan peran kepemimpinannya dalam meningkatkan mutu sekolah sebagai sekolah unggul. Luaran kegiatan ini berupaya meningkatkan pemahaman kepada 50 orang kepala sekolah tentang: 1) Kepemimpinan Kepala Sekolah di sekolah unggul secara berkelanjutan, mandiri, dan kontekstual; 2) Kepemimpinan Pembelajaran di sekolah unggul secara berkelanjutan, mandiri, dan kontekstual; 3) Kepemimpinan Religius di sekolah unggul secara berkelanjutan, mandiri, dan kontekstual; dan 4) Kepemimpinan Perubahan di sekolah unggul secara berkelanjutan, mandiri, dan kontekstual. Metode yang digunakan dalam kegiatan pengabdian ini adalah: a) pelatihan, dan b) pendampingan. Secara garis besar kegiatan penguatan kepemimpinan kepala sekolah menuju sekolah unggul ini dapat terlaksana dengan baik.